GAMBARAN STATUS SOSIAL EKONOMI PADA ANAK STUNTING USIA 24-59 BULAN DI WILAYAH KERJA PUKESMASSUNGAI RAYA DALAM KABUPATEN KUBU RAYA - Didik Hariyadi; Mulyanita; Tia Amelia (Media Gizi Khatulistiwa, 2025)
Background: Based on data from the Indonesia Nutrition Status Survey (SSGI) released by the Ministry of Health, in 2022, the prevalence of stunting in Indonesia decreased by 2.8 percentage points compared to 2021 from 24.4% to 21.6%. Currently, the prevalence of stunting in West Kalimantan reaches 17.8% according to SKI 2023. Objectives: To find out the overview of the socioeconomic status of parents in stunted children aged 24-59 months in the working area of the Sungai Raya Health Center in Sungai Raya District, Kubu Raya Regency. Method: This type of research is descriptive research where the number of samples obtained is 39 toddlers, then the data analysis used is by using univariate analysis, namely frequency distribution Result: Mother's knowledge of nutrition is 100%, Junior high school graduates' education is 59.0%, High school graduates' education is 51.3%, Farmers' parents' employment is 38.5% and housewives 94 %, The income level of stunted toddlers is relatively low with a percentage of 64% and the nutritional status of TB/U children (stunting) is the percentage of children with short status Conclusion: The Mother's knowledge of nutrition is excellent, Father's education level is mostly junior high school graduate while for the type of education mother are mostly high school graduates, Father's type of work is mostly working as farmers with While for mothers' jobs most of them are housewives, The majority of family income levels are relatively low and the nutritional status of children with TB/U (stunting) is the percentage of children with short nutritional status